2013
DOI: 10.1200/jco.2013.31.15_suppl.e18530
|View full text |Cite
|
Sign up to set email alerts
|

Does presence of chronic obstructive pulmonary disease (COPD) influence clinical behavior in patients with early-stage non-small cell lung cancer (ESNSCLC)?

Abstract: e18530 Background: CDPD and lung cancer sometimes occurs simultaneously. COPD has been recognized as an inflammatory disease and may potentially affect biology of the accompanying tumor. It is not fully understood whether presence of CDPD influences clinical characteristics, pathological findings and/or clinical outcomes in patients with ESNSCLC. Methods: Retrospective and consecutive data were collected from the medical records of patients who underwent surgical resections at Kinki-chuo Chest Medical Center,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…After initial screening based on titles and abstracts with predefined inclusion/exclusion criteria, 58 articles were identified for full-text review, of which 26 articles were identified for metaanalysis. 3,5,[13][14][15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Of these, 19 specifically reported the results on COPD, 3,5,13,14,16,20,[22][23][24]27,29,30,32-38 5 on emphysema, 17,21,26,28,31 and 2 on both COPD and emphysema 15,25 with lung cancer prognosis. Table 1 presents the characteristics of 21 studies for concomitant COPD and lung cancer survival.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After initial screening based on titles and abstracts with predefined inclusion/exclusion criteria, 58 articles were identified for full-text review, of which 26 articles were identified for metaanalysis. 3,5,[13][14][15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Of these, 19 specifically reported the results on COPD, 3,5,13,14,16,20,[22][23][24]27,29,30,32-38 5 on emphysema, 17,21,26,28,31 and 2 on both COPD and emphysema 15,25 with lung cancer prognosis. Table 1 presents the characteristics of 21 studies for concomitant COPD and lung cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents the characteristics of 21 studies for concomitant COPD and lung cancer survival. 3,5,[13][14][15][16]20,[22][23][24][25]27,29,30,[32][33][34][35][36][37][38] These studies were published between 2001 and 2015. Of these, six studies were conducted in the United States, 3,13,23,25,32,35 seven in European countries 5,15,16,29,30,33,34 and eight in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations